2013
DOI: 10.3109/08880018.2013.791738
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Radiation Necrosis in Pediatric Patients

Abstract: Radiation necrosis is a well-described toxicity following radiation therapy in the brain. There is little data regarding the incidence of radiation necrosis in pediatric patients. We retrospectively reviewed our experience with 101 children with solid brain tumors. Radiation necrosis was diagnosed by examination of magnetic resonance imaging. Median follow-up for all patients was 13 months (range 3-51). Radiation necrosis occurred in 5% (5/101) of cases with a median time to onset of 1.2 months. In three of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 9 publications
0
18
0
2
Order By: Relevance
“…In 1 study of 101 children treated with photon radiation therapy, 5% of patients developed radiation necrosis based on clinicoradiologic follow-up. 2 In another study of 49 patients with malignant brain tumors treated with photon radiation therapy, high-dose thiotepa, and autologous stem cell rescue, 37% of patients developed posttreatment abnormal brain imaging findings, which were defined broadly to include contrast-enhancing lesions, T2-weighted or FLAIR hyperintense lesions, hemorrhage, or subdural fluid, though the percentage of radiation necrosis was not reported. 3 In our series, 31% of patients developed radiation necrosis based on imaging, indicating a trend toward a higher incidence of necrosis with PBT compared with the incidence reported for photon radiation therapy, which was similar to the high percentage in a series of 17 patients treated with PBT, of whom 47% developed an imaging diagnosis of radiation necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1 study of 101 children treated with photon radiation therapy, 5% of patients developed radiation necrosis based on clinicoradiologic follow-up. 2 In another study of 49 patients with malignant brain tumors treated with photon radiation therapy, high-dose thiotepa, and autologous stem cell rescue, 37% of patients developed posttreatment abnormal brain imaging findings, which were defined broadly to include contrast-enhancing lesions, T2-weighted or FLAIR hyperintense lesions, hemorrhage, or subdural fluid, though the percentage of radiation necrosis was not reported. 3 In our series, 31% of patients developed radiation necrosis based on imaging, indicating a trend toward a higher incidence of necrosis with PBT compared with the incidence reported for photon radiation therapy, which was similar to the high percentage in a series of 17 patients treated with PBT, of whom 47% developed an imaging diagnosis of radiation necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This compares with radiation necrosis described at a median of 1.2 months (range, 0.5-8.0 months) and 8 months (range, 2-39 months) in 2 large series of patients with pediatric brain tumors treated with photon radiation therapy and a median time of 3.9 months in a smaller series of patients treated with PBT. 2,3 It remains uncertain which factors in patients with pediatric brain tumor account for the difference in time to development of radiation necrosis compared with adult patients, which is more typical at or greater than 12 months. 1,24 Based on the proposed pathogenesis of radiation necrosis, there may be differences in the vascular endothelium, progenitor cells, oligodendrocytes, microglia, local microenvironment, and inflammatory response in the developing brain compared with adults accounting for the differences in timing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of radiation necrosis in adults is reported between 5 and 10%. There is limited data on the incidence in children, but current studies report 3.7–5% risk, based largely on children with high‐grade brain tumors . A retrospective review of 236 children with medulloblastoma and other CNS embryonal tumors showed a necrosis incidence of 3.7% at 5 years .…”
Section: Discussionmentioning
confidence: 99%
“…Любопытно, что с возрастом в мозге крыс происходит снижение экспрессии провоспалительных медиаторов в ответ на лучевое воздействие [34]. В то же время существуют данные, указывающие на снижение риска развития лучевого некроза у взрослых пациентов по сравнению с детьми [48]. Таким образом, большое число многосторонних данных указывает на ключевую роль нейровоспалительных процессов в патогенезе развития разнообразных лучевых повреждений мозга, включая лучевой некроз и когнитивные нарушения.…”
Section: нейровоспалениеunclassified